Enhanced Efficiency for Biogas Production from Distillery Wastewater as Mixed with Molasses and Glycerol Waste in the Anaerobic Co-Digestion - Rattanadilok Na Phuket, Kiattisak; Srimachai, Tussanee; Luanunkarb, Saowarod; O-Thong, Sompong (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
This experiment was conducted to decide the impact of molasses and glycerol waste on upgraded methane production in anaerobic co-digestion with distillery wastewater. Co substrates used for biogas production in the anaerobic co-fermentation process of distillery wastewater (DW) were molasses (ML) and glycerol waste (GW). The co-substrate concentration in all batch experiments varied between 1% and 5% (v/v). To study the efficiency of biogas production, the optimal ratio was chosen for operation in the PFR continuous reactor. Optimization results indicated that anaerobic co-digestion of DW with 5% GW and 1% ML could improve biogas quality and quantity. HRT for 30 days allowed R2 (95% DW: 5% GW) to produce maximum methane production per 11 m3 CH4/m3 mixed wastewater, followed by R1 (99% DW: 1%). ML) 6 m3 CH4/m3 mixed wastewater and control (100% DW) could only produce 2.7 m3 CH4/m3 mixed wastewater methane. As co-substrates, GW and ML can be balanced to coordinate the C/N ratio and pH of DW. In particular, the C/N ratio of the mixed sewage can be balanced, and the concentration of ammonia nitrogen within an anaerobic digestion tank can be diluted. Therefore, GW can be used as an optimal co-substrate as it improves the C/N ratio, dilutes toxic compounds within DW, and provides lower prices, thus increasing the potential for methanogenesis within DW affected to increase biogas production.